Tunable layer-by-layer films containing hyaluronic acid and their interactions with CD44 - Amorim, Sara (2020)
We report on the development of layer-by-layer (LbL) constructs whose viscoelastic properties and bioactivity can be finely tuned by using polyanions of different size and/or crosslinking. As a polyanion we used hyaluronic acid (HA) â a multi-signaling biomolecule whose bioactivity depends on its molecular weight. We investigated the interplay between the mechanical properties of the LbL systems built using HA of different sizes and the specific HA-mediated biochemical interactions. We characterized the assembled materials and their interactions with CD44, the main HA receptor, by Quartz Crystal Microbalance with Dissipation (QCM-D), Surface Plasmon Resonance (SPR) and Atomic Force Microscopy (AFM). We observed that the presence of CD44 resulted in the disruption of the non-crosslinked multilayers, while crosslinked films remain stable and bind CD44 in a HA molecular weight and charge specific fashion.